Trials on the Environmental Education Processes as Reducing Cholinesterase Enzyme in Blood and Residues of Chemicals in Soil with sugarcane farmers in Phetchabun Province of Thailand (Journal of Pharmaceutical Negative Results, 2022)
This study was quasi- experimental research, and the objectives were to i) study behavior in practice for self- prevention in chemicals use before and after using environmental education processes, ii) compare cholinesterase enzyme in blood of sugarcane farmers before and after using environmental education processes, and iii) compare amount of chemical residues in soil in the sugarcane planting areas before and after using environmental education processes. The sample were the 36 sugarcane farmers whom had cholinesterase enzyme in blood equal to or more than risk level, and were selected by multi-stage sampling. Of these test kit used for the analysis of cholinesterase enzyme in blood with the reactive paper of the Department of Health (1997) and chemical residues in soil based on the standard of the Department of Health (1997) by the method of High-Performance Liquid Chromatography (HPLC) with the unit of mg/kg and reported according to the central laboratory.The comparisons of the behavior in practice for self-prevention in chemicals use revealed that after using environmental education processes, mean higher than before with a statistical significance level of 0.01. The comparisons of cholinesterase enzyme in blood of sugarcane farmers revealed that before trials, the most of them had a cholinesterase enzyme level at risk equal to 27 persons or 75.00 %, but after trials they were at a risk equal to 18 persons or 50.00 % which it was lower than before. The sample soil for the analysis of chemicals residues revealed that before trials found the organophosphate 72.15 mg/kg, carbamate 10.00 mg/kg, glyphosate 9.99 mg/kg, and paraquat 5.21 mg/kg which it was at an unsafe level, but after trials found that the organophosphate, carbamate, glyphosate, and paraquat, were at a safe level or not detected.